Treatment Results of Geotropic and Apogeotropic Horizontal Canal Benign Paroxysmal Positional Vertigo in a Tertiary Dizziness Clinic - Maas, Britta D. P. J.; van Leeuwen, Roeland B.; Masius-Olthof, Sylvia; van Benthem, Peter Paul G.; Bruintjes, Tjasse D. (Frontiers in Neurology, 2021)
Purpose: To determine the effectiveness of our treatment protocol for geotropic and apogeotropic horizontal canal benign paroxysmal positional vertigo (h-BPPV). Methods: We retrospectively evaluated patients with newly diagnosed geotropic and apogeotropic h-BPPV who visited our clinic between July 2017 and December 2019. Patients were treated according to our treatment protocol, which was implemented in 2017. Patients with geotropic h-BPPV were preferably treated with the Gufoni maneuver. In patients with apogeotropic h-BPPV we executed the modified Gufoni maneuver to achieve conversion to the geotropic type. We looked at the number of successful treatments and the number of recurrences within one year. Results: We included 102 patients with h-BPPV, 62 (61%) of whom were treated for geotropic h-BPPV. The ratio of apogeotropic to geotropic h-BPPV was 0.65. After the first visit, we observed resolution of horizontal canal BPPV in 71% and 63% of the geotropic and the apogeotropic group, respectively. After the second visit, this percentage increased to 92% for geotropic h-BPPV and 78% for apogeotropic h-BPPV. After one year of follow-up we determined a recurrence rate of 32% and 24% for the geotropic and apogeotropic group, respectively. Conclusion: With our treatment protocol we managed to achieve high rates of symptom resolution in the geotropic and apogeotropic type of h-BPPV with acceptable recurrence rates. We observed a relatively high ratio of apogeotropic h-BPPV to geotropic h-BPPV.